SELF-CONCEPT IN STUDENTS IN TEACHING PUBLIC SPEAKING - Dina Kristina (Jurnal Scientia, 2023)
Public speaking is a public communication skill that is important for college students to have to develop their self-value and quality in having good communication academically and socially. Thus, it has to be taught appropriately in formal education. When someone has more proficiency in their public speaking skills, they will have more confidence when speaking publicly in front of an audience and the confidence will affect their self-concept. This study aimed to identify the self-concept change before and after the teaching of public speaking to college students. The study employed a qualitative research design. The research subject is the 2022 batch of Public Speaking college students in the Faculty of Communication Studies at Universitas Bhayangkara Jakarta Raya. The study revealed that public speaking plays a crucial role in students’ self-concept change. Prior to the teaching of public speaking, the students had negative self-concepts with a variety of communication anxiety symptoms. After the teaching of public speaking, the students’ self-concepts were turned positive along with the development of their self-confidence and good communication skills, verbally and non-verbally.